2010
DOI: 10.1142/s1793830910000784
|View full text |Cite
|
Sign up to set email alerts
|

The Ramsey Number for a Linear Forest Versus Two Identical Copies of Complete Graphs

Abstract: Let H be a graph with the chromatic number h and the chromatic surplus s. A connected graph G of order n is called H-good if R(G, H) = (n - 1)(h - 1) + s. In this paper, we show that Pn is 2Km-good for n ≥ 3. Furthermore, we obtain the Ramsey number R(L, 2Km), where L is a linear forest. Moreover, we also give the Ramsey number R(L, Hm) which is an extension for R(kPn, Hm) proposed by Ali et al. [1], where Hm is a cocktail party graph on 2m vertices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…In particular, when G is a disjoint union of cycles then by using the results of Sudarsana et al [11] and Theorem 1.1 we obtain the Corollary 1.1 below for finding the exact value of Ramsey number R(G, tW 4 ).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In particular, when G is a disjoint union of cycles then by using the results of Sudarsana et al [11] and Theorem 1.1 we obtain the Corollary 1.1 below for finding the exact value of Ramsey number R(G, tW 4 ).…”
Section: Introductionmentioning
confidence: 81%
“…Let G be a graph containing all H-good components, the general formula for finding the exact value of Ramsey number R(G, H) have been found by Bielak [2] and Sudarsana et al [11]. In some particular graphs, showed by Stahl [10] and Baskoro et al [1].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Results without the assumption of sufficiently large number of vertices are also interesting. In [15], Sudarsana, Adiwijaya and Musdalifah showed that P n is 2K mgood for n ≥ 3 and m ≥ 2, and conjectured that any tree T n with n vertices is 2K m -good. Recently, Pokrovskiy and Sudakov [11] proved that for a fixed graph H, the path on n vertices with n ≥ 4v(H) is H-good.…”
Section: Introductionmentioning
confidence: 99%
“…By applying this result, Stahl [13] determined the Ramsey number of a forest versus Km. Concerning whether a tree is H-good for H being disjoint union of complete graphs, Chvátal and Harary [6] showed that any tree is 2K2-good, where tH denotes the union of t disjoint copies of graph H. Sudarsana, Adiwijaya and Musdalifah [15] proved that the n-vertex path Pn is 2Km-good for n ≥ 3 and m ≥ 2, and conjectured that any tree Tn with n vertices is 2Km-good. Recently, Pokrovskiy and Sudakov [11] proved that Pn is H-good for a graph with n ≥ 4v(H).…”
mentioning
confidence: 99%